Does postpartum depression affect employment? - Maria Elena Komodromou (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This paper examines the effect of postpartum depression (PPD) on maternal employment in the UK and assesses the extent of the direct and indirect link between PPD and maternal employment up to eleven years after the birth of the child. The study tests a range of factors (marital status, physical longstanding health problems, mental health problems, children's outcomes) as mediators in order to assess the indirect effect of PPD on maternal employment, utilising several waves of data from the Millennium Cohort Study. The findings are of significance to policy makers as they indicate that PPD has a direct effect on maternal employment 5 years after the birth of the child and an indirect effect after 7 and 11 years. The indirect effects are mediated primarily through subsequent maternal mental and physical health problems.
Keywords: J21; J13; J16; I14; 330; postpartum depression; maternal employment; health inequalities; KHB decomposition